Clinical and Laboratory Peculiarities of Chronic Active M. Epstein – I. Barr Virus Infection Course in Patients with Allergic Diseases - Zubchenko S.; Chopyak V. (Львівський клінічний вісник)
Introduction. In case of weak or insufficient immune response, activation of chronic M. Epstein – I. Barr virus infection initiates different pathological disorders, one of which is allergy. Aim. To specify the features of patients with allergic diseases and to investigate clinical and laboratory peculiarities of chronic active M. Epstein – I. Barr virus infection course. Materials and methods. Totally, 298 patients, who were consulted at Lviv regional medical center of clinical immunology and allergology in 2016-2017 years with prior stratification by the presence of allergic symptoms, were examined randomly. All patients underwent clinical, laboratory and instrumental, specific allergy tests. Detection of herpes virus infections was performed by the results of molecular and genetic investigations. In general, the research involved 62 patients with verified allergic diseases, who were infected only with M. Epstein – I. Barr virus (33 (53.3 %) females and 29 (46.7 %) males aged 28.6 ± 2.4 years). The diseases were verified based on ARIA (2016), GINA (2016-2017) criteria and unified clinical protocol “Atopic dermatitis” (2016). Results. Allergic diseases constituted 20.08 %. Verified persistent allergic rhinitis as well as sensitization with house dust mites, grass and spring trees were the most common. Polysensitization was detected in 75.80 % of individuals, and hyper-IgE syndrome in 50.00 %. Chronic active M. Epstein – I. Barr virus infection was detected in 48.38 % of patients with allergic diseases (1st group). Clinical signs of allergopathy in patients of the 1st group were manifested by rhino-conjunctivitis, cutaneous syndrome (p < 0.05), transitory syndrome of expiratory breathlessness (p < 0.05) and hyper-IgE-syndrome, namely with reliably higher IgE content (p < 0.05) compared to the patients with chronic active M. Epstein – I. Barr virus infection in latent phase (2nd group). In patients of the 1st group, polysensitization and the presence of allergopathy in close relatives were more common (p < 0.05), indicating the probability of genetic predisposition to allergic diseases (p < 0.05). Conclusions. The results of investigation prove the influence of chronic active M. Epstein – I. Barr virus infection on the course of allergic diseases in adults, and indicate the applicability and perspectives of the research in this direction.